Development of nanocomposite membranes for dairy wastewater treatment - Sisay Elias Jigar; László Zsuzsanna (2023)
A novel photocatalytic nanocomposite membrane was prepared successfully by blending. poly(vinylidene-fluoride) (PVDF) with TiO2, and/or carbon nanotube (CNT), and/or BiVO4 at various ratios in the membrane material via phase inversion method. The prepared membranes were evaluated for model or real dairy wastewater treatment. The membranes were characterized. by several surface characterization methods as SEM, AFM, XRD, and EDX. XRD and SEM measurements revealed that the nanoparticles were present as 200–300 nm-sized aggregates in the membrane, which increased the roughness of composite blended membranes (AFM results). EDX measurements exhibited that the proteins have covered a relatively large area of the pristine PVDF. membrane, resulting in a relatively high N/F ratio. Addition of TiO2, and/or carbon nanotube (CNT), and/or BiVO4 nanoparticles into the PVDF membrane material decreased the contact angle. of membrane surface, thus increased the hydrophilicity of modified blended membranes. In dead end cell BSA filtration experiment, PVDF/TiO2/CNT/BiVO4 nanocomposite blended membrane exhibited a pure water flux up to 150.52 Lm−2 h −1 which is two-fold higher than virgin membrane and a higher bovine serum albumin (BSA) rejection of about 97 %. Based on flux recovery ratio and flux the optimal CNT ratio in the PVDF/TiO2/CNT and BiVO4 in PVDF/TiO2/BiVO4 nanocomposite membrane was 2 % and 50 % respectively. More importantly, the PVDF /TiO2/CNT-BiVO4-50 (PTCB50) (containing 0.48 wt % TiO2, 0.02 wt % CNT and 0.5 wt % BiVO4) and PVDF/TiO2/BiVO4-50 (PTB50) (containing 0.5 wt % TiO2 and 0.5 wt % BiVO4 in PVDF) membrane exhibited a smaller irreversible fouling and a higher flux recovery ratio, revealing that blending with TiO2, and/or CNT, and/or BiVO4 could improve the self-cleaning under visible irradiation and the antifouling properties of PVDF membrane. The application of BPTB50 and B-PTCB50 membranes to treat real dairy wastewater were promising. They exhibited better antifouling and foulant degradation performance as compared to pristine membrane. However, the lower rejection performances of the membranes were due to ability of lactose to pass through the membranes which requires further treatment. Overall, the incorporation of nanoparticles in the polymer matrix enhanced the antifouling and foulant degradation performance. of the photocatalytic nanocomposite membrane to a remarkable extent.
A doktori munkám során poli(vinilidén-fluorid) (PVDF), TiO2, szén nanocső (CNT) és/vagy BiVO4 tartalmú új fotokatalitikus nanokompozit membránokat készítettem, fázisinverziós módszerrel. A kész membránok hatékonyságát modell vagy valós tejipari szennyvíz szűrése során vizsgáltam. A membránokat számos felületvizsgálati módszerrel jellemeztem, pl. SEM, AFM, XRD és EDX méréseket végeztem. Az XRD és SEM mérések kimutatták, hogy a nanorészecskék 200-300 nm-es aggregátumok formájában jelennek meg a membránban, ami növelte a kompozit kevert membránok felületi érdességét (AFM eredmények). Az EDX mérések azt mutatták, hogy a fehérjék viszonylag nagy területet fedtek le a PVDF membrán felületén, amely magas N/F arányhoz vezetett, amely a membrán módosításával jelentősen csökkenthető volt. A TiO2, szén nanocső (CNT) és/vagy BiVO4 nanorészecskék hozzáadása a PVDF membrán anyagához növelte a módosított membránok hidrofilitását. A PVDF/TiO2/CNT/BiVO4 nanokompozit membrán tiszta víz fuxusa 150,52 Lm−2 h−1 volt, ami kétszerese a nem módosított PVDF membránon mérhető értéknek, míg a membrán marha szérum albumin (BSA) visszatartása 97 % volt. Az membránok 1%-ban tartalmaztak nanorészecskéket, ezen belül az optimális CNT arány 2%, míg a BiVO4 optimális aránya 50% volt a fluxus-visszanyerési arány és az eltömődés-gátló hatás alapján. A módosított membránok kisebb irreverzibilis eltömődést és magasabb fluxus-visszanyerési arányt mutattak, bizonyítva, hogy a TiO2-dal és/vagy CNT-vel és/vagy BiVO4-tal való keverés javítja a membrán eltömődés-gátló tulajdonságát, illetve lehetővé teszi a látható fénnyel való tisztítását. A módosított membránok alkalmazása a valódi tejipari szennyvíz kezelésére szintén ígéretes volt; mind az eltömődés gátló hatásuk, mind a tisztíthatóságuk jobb volt a nem módosított PVDF membránhoz képest. Ugyanakkor, a magasabb laktóztartalmú szennyvizek esetében az ultraszűrő membránok nem elég hatékonyak, ezen esetekben a permeátum további tisztítására is szükség lehet. Összességében a polimer mátrixban lévő nanorészecskék figyelemre méltó mértékben növelték a membránok eltömődésgátló hatását és a lehetővé tették a membránok fotokatalitikus tisztítását látható fény alkalmazásával.
Disszertacio
Keywords: környezettudományok; Természettudományok; Föld- és kapcsolódó környezettudományok; Szennyvízkezelés